Method for producing thermally conductive sheet

By forming a coating layer with different adhesion properties on the surface of the thermally conductive sheet, the problems of uneven thickness and insufficient adhesion during the cutting process are solved, and the operability and reprocessability of the thermally conductive sheet are improved.

CN110739224BActive Publication Date: 2024-12-27SEKISUI CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201910625646.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-07-18
Filing Date
2019-07-11
Publication Date
2024-12-27
Estimated Expiration
2039-07-11

AI Technical Summary

Technical Problem

The existing thermally conductive sheets are difficult to uniformly thickness during cutting, resulting in surface concave and convexity, affecting heat conduction, and insufficient adhesion, resulting in poor operability and reprocessing.

Method used

By using a side release film with different non-adhesion and adhesion in the thermally conductive resin composition, the uncured resin is penetrated through the pressing process to form a coating layer, thereby imparting adhesion to the sheet surface, and controlling one side of the non-adhesion to maintain the non-adhesion by the stripping film .

Benefits of technology

The workability, operability and reprocessability of the thermally conductive sheet are improved, and the position accuracy and repeatability of the thermally conductive sheet when assembling electronic components and heat dissipation members are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110739224B_ABST
    Figure CN110739224B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for producing a thermally conductive sheet. The object of the present invention is to provide a method for producing a thermally conductive sheet that improves workability and reprocessability by imparting adhesiveness to one side of the thermally conductive sheet and imparting non-adhesiveness to the other side. The method for producing a thermally conductive sheet of the present invention includes the following steps: a step of forming a thermally conductive molded body by molding a thermally conductive resin composition containing a thermally conductive filler in a binder resin into a predetermined shape and curing it, a step of cutting the thermally conductive molded body into a sheet to form a molded body sheet, a step of attaching a release film to both sides of the molded body sheet, pressing the molded body sheet, thereby imparting adhesiveness to both sides of the molded body sheet by coating the uncured components of the binder resin that have seeped out of the sheet body of the molded body sheet, a step of peeling the release film from one side of the molded body sheet, removing the uncured components of the binder resin from one side, imparting non-adhesiveness, and a step of attaching a new release film to one side.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive sheet which is attached to electronic components and the like to improve the heat dissipation thereof. Background Art

[0002] As electronic devices become more high-performance, the density and mounting of electronic components such as semiconductor elements are becoming increasingly high. In order to dissipate the heat generated by electronic components constituting electronic devices more efficiently, thermally conductive sheets are used to be sandwiched between various heat sources (such as various devices such as LSI, CPU, transistor, LED) and heat sinks (such as heat sinks, heat sinks, etc.) to dissipate heat.

[0003] As a thermally conductive sheet, a thermally conductive sheet containing a thermally conductive filler such as an inorganic filler dispersed in a silicone resin is widely used. For such a heat dissipation component, it is required to further improve the thermal conductivity. Generally speaking, in order to achieve high thermal conductivity, this is addressed by increasing the filling rate of the inorganic filler blended in the polymer matrix. However, if the filling rate of the inorganic filler is increased, the flexibility is impaired, or powder falls off due to the high filling rate of the inorganic filler, so there is a limit to increasing the filling rate of the inorganic filler.

[0004] As inorganic fillers, for example, aluminum oxide, aluminum nitride, aluminum hydroxide, etc. can be cited. In addition, for the purpose of high thermal conductivity, flaky particles such as boron nitride and graphite, carbon fibers, etc. are sometimes filled in the polymer matrix. This is due to the anisotropy of the thermal conductivity of flaky particles, etc. For example, it is known that in the case of carbon fibers, the thermal conductivity is about 600 to 1200 W / mK in the fiber direction; in the case of boron nitride, the thermal conductivity is about 110 W / mK in the surface direction, and the thermal conductivity is about 2 W / mK in the direction perpendicular to the surface direction, which is anisotropic. In this way, the surface direction of the carbon fibers and flaky particles is the same as the thickness direction of the sheet, which is the direction of heat transfer. That is, by orienting the carbon fibers and flaky particles in the thickness direction of the sheet, the thermal conduction can be dramatically improved.

[0005] However, there is a problem that when a thermally conductive resin composition containing a thermally conductive filler in a polymer matrix is ​​molded and then cured to obtain a cured product, if the cured product cannot be cut into sheets with a uniform thickness, large uneven portions will be formed on the surface of the thermally conductive sheet. When the sheet is sandwiched between an electronic component and a heat dissipation member, the uneven portions will draw in air, preventing excellent heat conduction.

[0006] In addition, in the method of manufacturing a thermally conductive sheet by cutting a thermally conductive composition, there is a problem that the surface of the thermally conductive sheet formed by cutting has no tack (adhesiveness).

[0007] Therefore, for example, in Patent Documents 1 and 2, high flexibility is imparted by changing the ratio of agent A to agent B of silicone, and by pressing or sandwiching between PET films and leaving them to stand, components that do not contribute to the reaction seep out to impart viscosity, thereby improving the followability and adhesion to the adherend and reducing thermal resistance. In addition, since the thermally conductive sheet has viscosity, it has operability and workability when assembling electronic components and heat sinks.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 5766335

[0011] Patent Document 2: Japanese Patent No. 5752299

[0012] Patent Document 3: Japanese Patent No. 3498823

[0013] Patent Document 4: Japanese Patent Application Publication No. 2010-93077 Summary of the invention

[0014] Problems to be solved by the invention

[0015] Here, from the perspective of operability, workability, or reprocessability such as correcting positional deviation when assembling electronic components and heat dissipation components, or disassembling and reassembling for some reason after temporary assembly, the thermally conductive sheet is preferably a thermally conductive sheet with high adhesion on one side and low adhesion on the other side.

[0016] Therefore, it has been proposed to form a thermally conductive sheet from silicone rubber and a thermally conductive filler and then subject the surface of the sheet to a non-sticking treatment by ultraviolet irradiation (Patent Document 3).

[0017] In addition, it has been proposed that in an adhesive thermally conductive sheet containing an acrylic urethane resin containing a non-functional acrylic polymer and a thermally conductive filler, the mixing ratio of the acrylic urethane resin to the non-functional acrylic polymer is different between the surface layer and the back layer, and the two layers are coated in an overlapping manner, thereby making the adhesiveness of the front and back sides of the adhesive thermally conductive sheet different (Patent Document 4).

[0018] However, when ultraviolet irradiation is performed in order to reduce the adhesiveness of one side of a thermally conductive sheet as described in Patent Document 3, the layer responsible for thermal conductivity deteriorates.

[0019] In addition, as described in Patent Document 4, when the mixing ratio of the acrylic polyurethane resin and the non-functional acrylic polymer in the surface layer and the back layer is different and overlapping coating is performed, the surface layer and the back layer are easily mixed, making it difficult to change the adhesion between the surface layer and the back layer as desired.

[0020] In addition, as a method of making the adhesiveness of the front and back sides of the thermally conductive sheet different, when an adhesive thermally conductive layer is formed from an acrylic resin and a thermally conductive filler, a method of laminating a non-adhesive film on one side is also considered. However, in this case, the adhesion of the film surface to the article is extremely reduced, so the workability as a thermally conductive sheet is poor.

[0021] Therefore, an object of the present invention is to provide a method for producing a thermally conductive sheet in which workability and reprocessability are improved by imparting adhesiveness to one surface of the thermally conductive sheet and imparting non-adhesiveness to the other surface.

[0022] Methods for solving problems

[0023] In order to solve the above-mentioned problems, the present invention relates to a method for producing a thermally conductive sheet, wherein one side of a sheet body is non-adhesive and the other side is adhesive, and the method comprises the following steps: a step of forming a thermally conductive molded body by molding a thermally conductive resin composition containing a thermally conductive filler in a binder resin into a predetermined shape and curing the composition; a step of cutting the thermally conductive molded body into a sheet to form a molded body sheet; a step of attaching release films to both sides of the molded body sheet and pressing the molded body sheet to coat both sides of the molded body sheet with uncured components of the binder resin that have oozed out of the sheet body of the molded body sheet, thereby imparting adhesiveness to both sides of the molded body sheet; a step of peeling the release film from one side of the molded body sheet to remove the uncured components of the binder resin from the one side and imparting non-adhesiveness to the one side of the molded body sheet; and a step of attaching a new release film to the one side from which the uncured components of the binder resin have been removed.

[0024] Effects of the Invention

[0025] According to the present invention, a thermally conductive sheet having non-adhesive properties on one side of the sheet body and adhesive properties on the other side can be produced, and workability and reprocessability are improved, thereby achieving excellent handling properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a cross-sectional view showing a thermally conductive sheet to which the present invention is applied.

[0027] Figure 2 It is a perspective view showing an example of the process of cutting a thermally conductive formed body.

[0028] Figure 3 This is a cross-sectional view showing a step of pressing a molded body sheet to which a release film is attached.

[0029] Figure 4It is a cross-sectional view showing the step of forming a resin coating layer between the surface of the laminated molded body sheet and the release film.

[0030] Figure 5 It is a cross-sectional view showing the step of removing the third release film from one surface of the molded body sheet.

[0031] Figure 6 This is a cross-sectional view showing a state in which uncured components are removed from one surface of a molded body sheet.

[0032] Figure 7 is a cross-sectional view showing an example of a semiconductor device.

[0033] Explanation of symbols

[0034] 1 Thermally conductive sheet, 2 Sheet body, 3 First release film, 4 Second release film, 5 Resin coating layer, 6 Thermally conductive molded body, 7 Molded body sheet, 8 Third release film. DETAILED DESCRIPTION

[0035] Hereinafter, the manufacturing method of the thermally conductive sheet to which the present invention is applied will be described in detail with reference to the accompanying drawings. In addition, the present invention is not limited to the following embodiments, and various changes can be made without departing from the main purpose of the present invention. In addition, the accompanying drawings are schematic diagrams, and the ratios of various dimensions are sometimes different from the actual ratios. The specific dimensions should be determined with reference to the following description. In addition, of course, the drawings also contain parts with different dimensional relationships and ratios.

[0036] A method for producing a thermally conductive sheet to which the present invention is applied is a method for producing a thermally conductive sheet having a non-adhesive property on one side of a sheet body and an adhesive property on the other side, the method comprising the following steps: a step of forming a thermally conductive molded body by molding a thermally conductive resin composition containing a thermally conductive filler in a binder resin into a predetermined shape and curing the composition (step A); a step of cutting the thermally conductive molded body into a sheet to form a molded body sheet (step B); a step of attaching release films to both sides of the molded body sheet and pressing the molded body sheet to coat both sides of the molded body sheet with uncured components of the binder resin that have oozed out of the sheet body of the molded body sheet, thereby imparting adhesiveness to both sides of the molded body sheet (step C); a step of peeling the release film from one side of the molded body sheet to remove the uncured components of the binder resin from the one side and imparting non-adhesiveness to the one side of the molded body sheet (step D); and a step of attaching a new release film to the one side from which the uncured components of the binder resin have been removed (step E).

[0037] The thermally conductive sheet manufactured through the above process has an uncured component that does not contribute to the reaction of the above binder resin carried on the sheet body of the molded body sheet, and a part of the uncured component is forced to seep out to the sheet surface through the pressing process. The uncured component seeping out to the sheet surface is retained on the sheet surface by the tension acting between the release film and the sheet surface, forming a resin coating layer covering the sheet surface, thereby imparting adhesiveness to the sheet surface.

[0038] If the release film is removed from one surface of the sheet body from this state, the uncured components covering the one surface disappear, showing non-adhesiveness. It is speculated that this is because the uncured components that forcibly seeped out and remained between the release film and the release film due to the pressing process return to the sheet body by removing the release film.

[0039] Next, a new release film is attached to one surface of the sheet body from which the uncured components have disappeared. Even after the new release film is peeled off, the uncured components of the adhesive resin do not seep out of one surface of the thermally conductive sheet, and the non-adhesive property is maintained. Therefore, the thermally conductive sheet manufactured through the above process has non-adhesive properties on one side of the sheet body and adhesive properties on the other side, thereby improving workability, operability, and reprocessability.

[0040] [Composition of thermally conductive sheet]

[0041] Figure 1 The thermally conductive sheet 1 to which the present invention is applied is shown. The thermally conductive sheet 1 has a sheet body 2 formed by curing a binder resin containing at least a polymer matrix component and a thermally conductive filler. A first release film 3 is adhered to one side 2a of the sheet body 2. A second release film 4 is adhered to the other side 2b of the sheet body 2 and is coated with uncured components of the binder resin that have seeped out of the sheet body 2, thereby forming a resin coating layer 5.

[0042] One side 2a of the thermally conductive sheet 1 is non-adhesive and maintains the non-adhesive property even after peeling off the first release film 3. The other side 2b of the thermally conductive sheet 1 is adhesive due to the resin coating layer 5, and can be attached to a predetermined position by peeling off the second release film during use.

[0043] Thus, the thermally conductive sheet 1 has excellent reworkability, such as correcting positional deviation when assembling electronic components and heat dissipating members or being able to be disassembled and reassembled for some reason after temporary assembly, and has excellent workability and operability due to the non-adhesive side 2a.

[0044] [Polymer matrix component]

[0045] The polymer matrix component constituting the sheet body 2 is a polymer component serving as a base material of the thermally conductive sheet 1. The type thereof is not particularly limited, and a known polymer matrix component can be appropriately selected. For example, a thermosetting polymer can be cited as one of the polymer matrix components.

[0046] As the above-mentioned thermosetting polymer, for example, crosslinked rubber, epoxy resin, polyimide resin, bismaleimide resin, benzocyclobutene resin, phenolic resin, unsaturated polyester, diallyl phthalate resin, silicone resin, polyurethane, polyimide silicone, thermosetting polyphenylene ether, thermosetting modified polyphenylene ether, etc. can be mentioned. These can be used alone or in combination of two or more.

[0047] In addition, examples of the crosslinked rubber include natural rubber, butadiene rubber, isoprene rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-propylene rubber, chlorinated polyethylene, chlorosulfonated polyethylene, butyl rubber, halogenated butyl rubber, fluororubber, urethane rubber, acrylic rubber, polyisobutylene rubber, silicone rubber, etc. These may be used alone or in combination of two or more.

[0048] Among these thermosetting polymers, silicone resins are preferably used because of their excellent molding processability and weather resistance, and their adhesion and conformability to electronic components. The silicone resin is not particularly limited, and the type of silicone resin can be appropriately selected according to the purpose.

[0049] From the viewpoint of obtaining the above-mentioned molding processability, weather resistance, adhesion, etc., the above-mentioned silicone resin is preferably a silicone resin composed of a main agent of liquid silicone gel and a curing agent. Examples of such silicone resins include addition reaction type liquid silicone resins and heat-curable kneaded silicone resins that use peroxide for vulcanization. Among them, as a heat dissipation component of an electronic device, since the heat-generating surface of the electronic component and the heat sink surface are required to have good adhesion, an addition reaction type liquid silicone resin is particularly preferred.

[0050] As the addition reaction type liquid silicone resin, it is preferable to use a two-component addition reaction type silicone resin having a polyorganosiloxane having a vinyl group as a main agent and a polyorganosiloxane having a Si—H group as a curing agent.

[0051] Here, the liquid silicone component includes a silicone liquid A component as a main agent and a silicone liquid B component including a curing agent, and the mixing ratio of the silicone liquid A component to the silicone liquid B component is preferably a silicone liquid A component containing a larger amount of the silicone liquid B component than that of the silicone liquid B component. Thus, the thermally conductive sheet 1 can impart flexibility to the sheet body 2, and the uncured components of the binder resin (polymer matrix component) can be exuded onto the surfaces 2a and 2b of the sheet body 2 by the pressing process, and a resin coating layer 5 is formed between the second release film 4 and the other surface 2b.

[0052] The content of the polymer matrix component in the thermally conductive sheet of the present invention is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoint of ensuring the moldability and adhesion of the sheet, it is preferably about 15% to 50% by volume, and more preferably 20% to 45% by volume.

[0053] [Thermal conductive filler]

[0054] The thermally conductive filler included in the thermally conductive sheet 1 is a component for improving the thermal conductivity of the sheet. The type of thermally conductive filler is not particularly limited as long as it is a material with high thermal conductivity, and examples thereof include fibrous thermally conductive fillers such as carbon fibers, metals such as silver, copper, and aluminum, and ceramics such as aluminum oxide, aluminum nitride, silicon carbide, and graphite. Among these fibrous thermally conductive fillers, carbon fibers are preferably used in order to obtain higher thermal conductivity.

[0055] In addition, the thermally conductive filler may be used alone or in combination of two or more. Furthermore, when two or more thermally conductive fillers are used, they may all be fibrous thermally conductive fillers or a fibrous thermally conductive filler may be used in combination with a thermally conductive filler of another shape.

[0056] There is no particular restriction on the type of the above-mentioned carbon fiber, and it can be appropriately selected according to the purpose. For example, pitch-based carbon fiber, PAN-based carbon fiber, carbon fiber obtained by graphitizing PBO fiber, carbon fiber synthesized by arc discharge method, laser evaporation method, CVD method (chemical vapor growth method), CCVD method (catalyst chemical vapor growth method) etc. can be used. Among them, from the aspect of obtaining high thermal conductivity, carbon fiber obtained by graphitizing PBO fiber and pitch-based carbon fiber are more preferred.

[0057] In addition, the carbon fiber may be used after a part or all of it has been subjected to surface treatment as required. Examples of the surface treatment include oxidation treatment, nitridation treatment, nitration, sulfonation, or treatment in which metals, metal compounds, organic compounds, etc. are attached or bonded to the functional groups introduced to the surface by these treatments or to the surface of the carbon fiber. Examples of the functional groups include hydroxyl, carboxyl, carbonyl, nitro, amino, etc.

[0058] Furthermore, the average fiber length (average major axis length) of the above-mentioned carbon fibers can be appropriately selected without particular limitation. From the perspective of ensuring high thermal conductivity, the average fiber length is preferably in the range of 50 μm to 300 μm, more preferably in the range of 75 μm to 275 μm, and particularly preferably in the range of 90 μm to 250 μm.

[0059] Furthermore, the average fiber diameter (average minor axis length) of the carbon fibers can be appropriately selected without particular limitation, but is preferably in the range of 4 μm to 20 μm, more preferably in the range of 5 μm to 14 μm, from the viewpoint of surely obtaining high thermal conductivity.

[0060] The aspect ratio (average major axis length / average minor axis length) of the carbon fibers is preferably 8 or more, and more preferably 9 to 30, from the viewpoint of reliably obtaining high thermal conductivity. If the aspect ratio is less than 8, the fiber length (major axis length) of the carbon fibers is short, so there is a concern that thermal conductivity may be reduced. On the other hand, if the aspect ratio exceeds 30, dispersibility in the thermally conductive sheet is reduced, so there is a concern that sufficient thermal conductivity may not be obtained.

[0061] Here, the average major axis length and the average minor axis length of the carbon fibers can be measured, for example, using a microscope, a scanning electron microscope (SEM), or the like, and the average value can be calculated from a plurality of samples.

[0062] The content of the fibrous thermally conductive filler in the thermally conductive sheet 1 is not particularly limited and can be appropriately selected according to the purpose, but is preferably 4% to 40% by volume, and more preferably 5% to 35% by volume. If the content is less than 4% by volume, it may be difficult to obtain a sufficiently low thermal impedance, and if it exceeds 40% by volume, it may affect the moldability of the thermally conductive sheet 1 and the orientation of the fibrous thermally conductive filler. In addition, the content of the thermally conductive filler including the fibrous thermally conductive filler in the thermally conductive sheet 1 is preferably 15% to 75% by volume.

[0063] [Inorganic fillers]

[0064] The thermally conductive sheet 1 may further contain an inorganic filler as a thermally conductive filler. By containing an inorganic filler, the thermal conductivity of the thermally conductive sheet 1 can be further improved, and the strength of the sheet can be improved. As the above-mentioned inorganic filler, the shape, material, average particle size, etc. are not particularly limited and can be appropriately selected according to the purpose. As the above-mentioned shape, for example, spherical, elliptical, blocky, granular, flat, needle-shaped, etc. can be cited. Among them, from the perspective of filling, spherical and elliptical shapes are preferred, and spherical shapes are particularly preferred.

[0065] As the material of the above-mentioned inorganic filler, for example, aluminum nitride (aluminum nitride: AlN), silicon dioxide, aluminum oxide (Aluminum oxide), boron nitride, titanium dioxide, glass, zinc oxide, silicon carbide, silicon (silicon), silicon oxide, metal particles, etc. can be mentioned. They can be used alone or in combination of two or more. Among them, aluminum oxide, boron nitride, aluminum nitride, zinc oxide, and silicon dioxide are preferred. From the aspect of thermal conductivity, aluminum oxide and aluminum nitride are particularly preferred.

[0066] The inorganic filler may be a surface-treated inorganic filler. If the inorganic filler is treated with a coupling agent as the surface treatment, the dispersibility of the inorganic filler is improved, and the flexibility of the thermally conductive sheet is improved.

[0067] The average particle size of the inorganic filler can be appropriately selected according to the type of inorganic material, etc. When the inorganic filler is alumina, the average particle size is preferably 1 μm to 10 μm, more preferably 1 μm to 5 μm, and particularly preferably 4 μm to 5 μm. If the average particle size is less than 1 μm, the viscosity may increase and the mixing may become difficult. On the other hand, if the average particle size exceeds 10 μm, the thermal impedance of the thermally conductive sheet 1 may increase.

[0068] Furthermore, when the inorganic filler is aluminum nitride, the average particle size is preferably 0.3 μm to 6.0 μm, more preferably 0.3 μm to 2.0 μm, and particularly preferably 0.5 μm to 1.5 μm. If the average particle size is less than 0.3 μm, the viscosity may increase and mixing may become difficult. If it exceeds 6.0 μm, the thermal impedance of the thermally conductive sheet 1 may increase.

[0069] The average particle size of the inorganic filler can be measured, for example, using a particle size distribution meter or a scanning electron microscope (SEM).

[0070] [Other ingredients]

[0071] The thermally conductive sheet 1 may contain other components as appropriate according to the purpose in addition to the above-mentioned polymer matrix component and thermally conductive filler. Examples of other components include magnetic metal powder, thixotropy imparting agent, dispersant, curing accelerator, retarder, micro thickener, plasticizer, flame retardant, antioxidant, stabilizer, colorant, etc. In addition, electromagnetic wave absorption performance may be imparted to the thermally conductive sheet 1 by adjusting the content of the magnetic metal powder.

[0072] [Process for producing thermally conductive sheet]

[0073] [Process A]

[0074] Next, the manufacturing process of the thermally conductive sheet 1 is described. As described above, the manufacturing process of the thermally conductive sheet 1 to which the present invention is applied includes step A, that is, the step of molding a thermally conductive resin composition containing a thermally conductive filler in a binder resin into a predetermined shape and curing it to form a thermally conductive molded body.

[0075] In step A, the polymer matrix component, the thermally conductive filler, and other components as appropriate are mixed to prepare a thermally conductive resin composition. The steps of mixing and preparing the components are not particularly limited, and for example, a thermally conductive filler, an appropriate inorganic filler, a magnetic metal powder, and other components are added to the polymer matrix component and mixed to prepare the thermally conductive resin composition.

[0076] Next, a fibrous thermally conductive filler such as carbon fiber is oriented in one direction. The method for orienting the filler is not particularly limited as long as it can be oriented in one direction. For example, by extruding or pressing the thermally conductive resin composition into a hollow mold under high shear force, the fibrous thermally conductive filler can be oriented in one direction relatively easily, so that the orientation of the fibrous thermally conductive filler is the same (within ±10°).

[0077] As the method of extruding or pressing the thermally conductive resin composition into a hollow mold under high shear force, specifically, an extrusion molding method or a mold molding method can be cited. When the thermally conductive resin composition is extruded from the die head in the extrusion molding method, or when the thermally conductive resin composition is pressed into the mold in the mold molding method, the thermally conductive resin composition flows, and the fibrous thermally conductive filler is oriented along the flow direction. At this time, if a slit is installed at the front end of the die head, it is easier to orient the fibrous thermally conductive filler.

[0078] The thermally conductive resin composition extruded or pressed into a hollow mold is molded into a block shape corresponding to the shape and size of the mold, and the polymer matrix component is cured while maintaining the orientation of the fibrous thermally conductive filler, thereby forming a thermally conductive molded body. The so-called thermally conductive molded body refers to a sheet-cutting base material (molded body) that is a raw material of the thermally conductive sheet 1 obtained by cutting into a predetermined size.

[0079] The size and shape of the hollow mold and the thermally conductive molded body can be determined according to the required size and shape of the thermally conductive sheet 1, and can be, for example, a rectangular parallelepiped having a longitudinal dimension of 0.5 cm to 15 cm and a lateral dimension of 0.5 cm to 15 cm. The length of the rectangular parallelepiped can be determined as required.

[0080] The method and conditions for curing the polymer matrix component can be changed according to the type of the polymer matrix component. For example, when the polymer matrix component is a thermosetting resin, the curing temperature during heat curing can be adjusted. Furthermore, when the thermosetting resin contains a main component of liquid silicone gel and a curing agent, it is preferably cured at a curing temperature of 80°C to 120°C. In addition, there is no particular limitation on the curing time during heat curing, and it can be set to 1 hour to 10 hours.

[0081] Here, in step A, not all of the polymer matrix component is cured, but uncured components are supported. The uncured components seep out to the surface of the sheet in the step of pressing the molded sheet described later, and form a resin coating layer having adhesiveness.

[0082] [Process B]

[0083] The manufacturing process of the thermally conductive sheet 1 to which the present invention is applied is as follows: Figure 2 As shown, the process includes step B, i.e., cutting the thermally conductive molded body 6 into sheets to form molded body sheets 7. In step B, the thermally conductive molded body 6 is cut into sheets at an angle of 0° to 90° with respect to the long axis direction of the oriented fibrous thermally conductive filler.

[0084] The thermally conductive molded body 6 is cut using a cutting device. The cutting device is not particularly limited as long as it can cut the thermally conductive molded body 6, and a known cutting device can be used as appropriate. For example, an ultrasonic cutter, a planer, etc. can be used.

[0085] The thickness of the molded body sheet 7 is the thickness of the sheet body 2 of the thermally conductive sheet 1 , and can be appropriately set according to the application of the thermally conductive sheet 1 , and is, for example, 0.2 mm to 0.5 mm.

[0086] In the step B, the plurality of molded body pieces 7 may be cut into smaller pieces by providing cuts to the molded body pieces 7 cut out from the thermally conductive molded body 6 .

[0087] [Process C]

[0088] The manufacturing process of the thermally conductive sheet 1 to which the present invention is applied is as follows: Figure 3 As shown, the process includes step C, that is, pasting the third release film 8 on one side of the molded body sheet 7 and pasting the second release film 4 on the other side, pressing the molded body sheet 7, thereby utilizing the uncured components of the adhesive resin that seeps out from the sheet body of the molded body sheet 7 to cover both sides of the molded body sheet 7, thereby imparting adhesiveness to both sides of the molded body sheet 7.

[0089] For example, PET films are used as the second release film 4 and the third release film 8. In addition, the second release film 4 and the third release film 8 may be subjected to a release treatment on the adhesive surface facing the surface of the molded body sheet 7.

[0090] The pressing may be performed, for example, using a pair of pressing devices formed of a flat plate and a flat-surface pressing head. Alternatively, the pressing may be performed using nip rollers.

[0091] There is no particular restriction on the pressure during the above-mentioned pressing, and it can be appropriately selected according to the purpose. If it is too low, the thermal impedance tends to remain unchanged compared to the case where pressing is not performed. If it is too high, the sheet tends to stretch. Therefore, it is preferably set to a pressure range of 0.1MPa to 100MPa, and more preferably set to a pressure range of 0.5MPa to 95MPa.

[0092] Here, as described above, in the thermally conductive molded body 6, not all of the polymer matrix components are cured, but the sheet body of the molded body sheet 7 carries uncured components of the binder resin (polymer matrix component), such as Figure 4 As shown in the figure, a part of the uncured components is forced to seep out to the sheet surface by the pressing process. The uncured components seeping out to the sheet surface are held on the sheet surface by the tension acting between the second release film 4 and the third release film 8, forming a resin coating layer 5 that covers the entire sheet surface with a uniform thickness, thereby imparting adhesiveness to the sheet surface.

[0093] Furthermore, by going through the pressing step, the surface of the molded body sheet is smoothed, the adhesion of the thermally conductive sheet 1 is enhanced, and the interface contact resistance under light load can be reduced.

[0094] [Process D]

[0095] The manufacturing process of the thermally conductive sheet 1 to which the present invention is applied is as follows: Figure 5 , Figure 6 As shown, the process includes step D, that is, a step of peeling the third release film 8 from one side of the molded body sheet 7 to remove the uncured components of the binder resin from the one side and imparting non-adhesiveness to the one side of the molded body sheet.

[0096] If the third release film 8 is removed from one side of the sheet body, the uncured components covering the one surface disappear, showing non-adhesiveness. This is presumably because the uncured components that forcibly seeped out and were retained between the third release film 8 and the sheet body during the pressing process return to the sheet body by removing the third release film 8.

[0097] After peeling off the third release film 8, the molded body sheet 7 is left to stand at room temperature and atmospheric pressure until the uncured components disappear from one side. In addition, after peeling off the third release film 8, a predetermined time, such as several minutes to several tens of minutes, is required until the uncured components disappear from one side, which varies depending on the polymer matrix components constituting the uncured components, the amount of the uncured components that ooze out to one side, etc.

[0098] In the step D, the molded body sheet 7 may be left to stand while being heated and dried in an oven, an industrial dryer, or the like, or left to stand in a reduced pressure atmosphere, or left to stand in an environment using both, thereby removing the uncured components of the binder resin from one side of the molded body sheet 7. This can be expected to promote the disappearance of the uncured components from one side of the molded body sheet 7.

[0099] In addition, the peel strength of the third release film 8 attached to one side can be made higher than the peel strength of the second release film 4 attached to the other side. The uncured component that oozes out to one side is a component that disappears or is removed, and the necessity of the third release film 8 being subjected to a peeling treatment is low, and the peel strength can be higher than the second release film 4 attached to the other side.

[0100] [Process E]

[0101] The manufacturing process of the thermally conductive sheet 1 to which the present invention is applied includes a step E of attaching a first release film 3 different from a third release film 8 to one side of the molded body sheet from which the uncured components of the binder resin have been removed. Figure 1 As shown, the thermally conductive sheet 1 includes a sheet body 2 whose one surface 2 a has non-adhesive properties and whose other surface 2 b has adhesive properties.

[0102] Even after the first release film 3 is peeled off, the uncured components of the adhesive resin do not seep out from the one surface 2a of the thermally conductive sheet 1, and the non-adhesive property is maintained. Therefore, the thermally conductive sheet 1 manufactured through the above-mentioned process has non-adhesive properties on one surface 2a of the sheet body 2 and adhesive properties on the other surface 2b, which can improve the handling, workability, and reprocessability.

[0103] [Example of use]

[0104] In actual use, the thermally conductive sheet 1 is peeled off from the first and second release films and mounted inside electronic components such as semiconductor devices or various electronic devices. At this time, one side 2a of the sheet body 2 of the thermally conductive sheet 1 is imparted with non-adhesiveness and the other side 2b is imparted with adhesiveness, so that the sheet body 2 has excellent handling properties and excellent reprocessability such as correcting positional deviation when assembling the electronic component and the heat dissipation member or disassembling and reassembling after temporary assembly for some reason.

[0105] The thermally conductive sheet 1 is, for example, Figure 7As shown, the semiconductor device 50 is mounted in various electronic devices and is sandwiched between a heat source and a heat dissipation member. Figure 7 The semiconductor device 50 shown has at least an electronic component 51, a heat spreader 52, and a thermally conductive sheet 1, and the thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the electronic component 51. By using the thermally conductive sheet 1, the semiconductor device 50 has high heat dissipation properties, and also has an excellent electromagnetic wave suppression effect depending on the content of the magnetic metal powder in the binder resin.

[0106] The electronic component 51 is not particularly limited and can be appropriately selected according to the purpose. For example, various semiconductor components such as CPU, MPU, graphics processing element, image sensor, antenna element, battery, etc. can be cited. The heat spreader 52 is not particularly limited as long as it is a component that dissipates the heat generated by the electronic component 51, and can be appropriately selected according to the purpose. The thermal conductive sheet 1 is clamped between the thermal spreader 52 and the electronic component 51. In addition, the thermal conductive sheet 1 is clamped between the thermal spreader 52 and the heat sink 53, thereby constituting a heat dissipation component that dissipates the heat of the electronic component 51 together with the thermal spreader 52.

[0107] The installation position of the thermal conductive sheet 1 is not limited to between the heat spreader 52 and the electronic component 51, or between the heat spreader 52 and the heat sink 53, and can be appropriately selected according to the configuration of the electronic device or semiconductor device. In addition, as a heat dissipation component, in addition to the heat spreader 52 and the heat sink 53, any heat dissipation component that conducts heat generated from a heat source to the outside can be used, and examples thereof include a heat sink, a cooler, a chip holder, a printed circuit board, a cooling fan, a Peltier element, a heat pipe, a metal cover, a housing, and the like.

[0108] [Shape retention, reliability]

[0109] Furthermore, the thermally conductive sheet 1 is required to maintain its shape when the first release film 3 and the second release film 4 are peeled off during actual use, and to suppress creep behavior even in a high temperature environment with a certain load by being sandwiched between an electronic component and a heat dissipating member, thereby achieving long-term reliability.

[0110] Therefore, in the thermally conductive sheet 1 , the blending ratio of the silicone A liquid component and the silicone B liquid component of the binder resin can be appropriately adjusted to set the flexibility of the sheet body 2 in a high temperature environment with a certain load applied.

[0111] For example, a circular thermally conductive sheet 1 with a diameter of 20 mm and a thickness of 0.3 mm is clamped by a cylindrical clamp with a diameter of 20 mm and a height of 12 mm, and the pressure is adjusted so as to apply 4.0 kgf / cm 2After the load was applied, the thermal conductive sheet 1 was left to stand at 80°C for 72 hours, and the distance of protrusion from one end surface of the jig was 1.3 mm or less, which was 5% or less of the diameter (20 mm) of the cylindrical jig.

[0112] Therefore, when the first release film 3 and the second release film 4 are peeled off during actual use, the thermally conductive sheet 1 can maintain its shape without being stretched, deformed, or even broken by the release films 3 and 4. In addition, the thermally conductive sheet 1 can suppress creep behavior in a high temperature environment with a certain load applied, and maintain long-term reliability.

[0113] Example

[0114] Next, examples of the present invention will be described.

[0115] [Example 1]

[0116] In a two-component addition reaction type liquid silicone, 23 volume % of aluminum nitride particles with an average particle size of 1 μm and 20 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 22 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 17.5 vol %:17.5 vol %. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall, and after being molded into a 50 mm square silicone molded body, it was heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the peeling film was peeled off and the product was cut with a slicer to a thickness of 0.5 mm. The cut molded body sheet was sandwiched with a peeling film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87°C, and a time of 3 minutes to produce a molded body sheet. After pressing, the peeling film on one side was peeled off and the product was left to stand for 10 minutes to produce a sample of a thermally conductive sheet.

[0117] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0118] The sample shape is processed into a thickness of 0.5mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 0.6 mm.

[0119] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.35°C·cm 2 / W.

[0120] [Example 2]

[0121] In a two-component addition reaction type liquid silicone, 23 volume % of aluminum nitride particles with an average particle size of 1 μm and 20 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 22 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 17.5 vol %:17.5 vol %. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall, and after being molded into a 50 mm square silicone molded body, it was heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the peeling film was peeled off and the product was cut with a slicer to a thickness of 0.3 mm. The cut molded body sheet was sandwiched with a peeling film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87°C, and a time of 3 minutes to produce a molded body sheet. After pressing, the peeling film on one side was peeled off and the product was left to stand for 10 minutes to produce a sample of a thermally conductive sheet.

[0122] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0123] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 0.6 mm.

[0124] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.30℃·cm 2 / W.

[0125] [Example 3]

[0126] In a two-component addition reaction type liquid silicone, 23 volume % of aluminum nitride particles with an average particle size of 1 μm and 20 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 22 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 17.8 vol %:17.2 vol %. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall, and after being molded into a 50 mm square silicone molded body, it was heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the peeling film was peeled off and the product was cut with a slicer to a thickness of 0.3 mm. The cut molded body sheet was sandwiched with a peeling film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87°C, and a time of 3 minutes to produce a molded body sheet. After pressing, the peeling film on one side was peeled off and the product was left to stand for 10 minutes to produce a sample of a thermally conductive sheet.

[0127] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0128] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 0.8 mm.

[0129] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.29°C·cm 2 / W.

[0130] [Example 4]

[0131] In a two-component addition reaction type liquid silicone, 23 volume % of aluminum nitride particles with an average particle size of 1 μm and 20 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 22 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 18.2 vol %:16.8 vol %. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall to form a 50 mm square silicone molded body, and then heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the peeling film was peeled off and the product was cut with a slicer to a thickness of 0.3 mm. The cut molded body sheet was sandwiched with a peeling film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87°C, and a time of 3 minutes to produce a molded body sheet. After pressing, the peeling film on one side was peeled off and the product was left to stand for 10 minutes to produce a sample of a thermally conductive sheet.

[0132] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0133] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 1.0 mm.

[0134] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.28°C·cm 2 / W.

[0135] [Example 5]

[0136] In a two-component addition reaction type liquid silicone, 24 volume % of aluminum nitride particles with an average particle size of 1 μm and 22 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 25 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 15.1 vol%:13.9 vol%. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall to form a 50 mm square silicone molded body, and then heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the peeling film was peeled off and the product was cut with a slicer to a thickness of 0.3 mm. The cut molded body sheet was sandwiched with a peeling film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87°C, and a time of 3 minutes to produce a molded body sheet. After pressing, the peeling film on one side was peeled off and the product was left to stand for 10 minutes to produce a sample of a thermally conductive sheet.

[0137] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0138] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 0.7 mm.

[0139] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.26°C·cm 2 / W.

[0140] [Example 6]

[0141] In a two-component addition reaction type liquid silicone, 28 volume % of aluminum nitride particles with an average particle size of 1 μm and 23 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 20 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 15.1 vol %:13.9 vol %. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall, and after being molded into a 50 mm square silicone molded body, it was heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the peeling film was peeled off and the product was cut with a slicer to a thickness of 0.3 mm. The cut molded body sheet was sandwiched with a peeling film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87°C, and a time of 3 minutes to produce a molded body sheet. After pressing, the peeling film on one side was peeled off and the product was left to stand for 10 minutes to produce a sample of a thermally conductive sheet.

[0142] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0143] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 0.9 mm.

[0144] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.38°C·cm 2 / W.

[0145] [Example 7]

[0146] In a two-component addition reaction type liquid silicone, 42 volume % of alumina particles with an average particle size of 5 μm coupled with a silane coupling agent and 23 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler are mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 17.5 vol%:17.5 vol%. The obtained silicone composition is extruded in a hollow quadrangular prism-shaped mold (50 mm × 50 mm) with a peeling film attached along the inner wall, and after being formed into a 50 mm square silicone molded body, it is heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product is taken out from the hollow quadrangular prism-shaped mold, the peeling film is peeled off and cut with a slicer to a thickness of 0.3 mm. The cut molded sheet was sandwiched with a release film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87° C., and a time of 3 minutes to obtain a molded sheet. After pressing, the release film on one side was peeled off and the sheet was left to stand for 10 minutes to prepare a thermally conductive sheet sample.

[0147] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0148] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 0.9 mm.

[0149] For the sample, a 1.5 kgf / cm 2The thermal impedance was measured with a load of 0.40℃·cm 2 / W.

[0150] [Example 8]

[0151] In a two-component addition reaction type liquid silicone, 23 volume % of aluminum nitride particles with an average particle size of 1 μm and 20 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 22 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 18.5 vol %:16.5 vol %. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall, and after being molded into a 50 mm square silicone molded body, it was heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the peeling film was peeled off and the product was cut with a slicer to a thickness of 0.3 mm. The cut molded body sheet was sandwiched with a peeling film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87°C, and a time of 3 minutes to produce a molded body sheet. After pressing, the peeling film on one side was peeled off and the product was left to stand for 10 minutes to produce a sample of a thermally conductive sheet.

[0152] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0153] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 1.1 mm.

[0154] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.25°C·cm 2 / W.

[0155] [Example 9]

[0156] In a two-component addition reaction type liquid silicone, 23 volume % of aluminum nitride particles with an average particle size of 1 μm and 20 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 22 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 19.2 vol %:15.8 vol %. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall, and after being molded into a 50 mm square silicone molded body, it was heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the peeling film was peeled off and the product was cut with a slicer to a thickness of 0.3 mm. The cut molded body sheet was sandwiched with a peeling film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87°C, and a time of 3 minutes to produce a molded body sheet. After pressing, the peeling film on one side was peeled off and the product was left to stand for 10 minutes to produce a sample of a thermally conductive sheet.

[0157] Table 1 shows the evaluation results of the samples of the thermally conductive sheet. When one side of the sample from which the release film was peeled off was placed on a SUS plate inclined at 45°, the sample moved, thereby confirming that the stickiness on one side disappeared. Then, it was confirmed that even if a newly prepared release film was placed on one side of the sample, the stickiness did not recover. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side had stickiness.

[0158] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 1.3 mm.

[0159] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.24°C·cm 2 / W.

[0160] [Comparative Example 1]

[0161] In a two-component addition reaction type liquid silicone, 23 volume % of aluminum nitride particles with an average particle size of 1 μm and 20 volume % of alumina particles with an average particle size of 5 μm, which were coupled with a silane coupling agent, and 22 volume % of pitch-based carbon fibers with an average fiber length of 150 μm as a fibrous thermal conductive filler were mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and the ratio of silicone agent A to agent B is 15.8 vol %:19.2 vol %. The obtained silicone composition was extruded in a hollow quadrangular prism-shaped mold (50 mm×50 mm) with a release-treated film attached along the inner wall, and after being molded into a 50 mm square silicone molded body, it was heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product was taken out from the hollow quadrangular prism-shaped mold, the release-treated film was peeled off and the product was cut with a slicer to a thickness of 0.3 mm. The cut molded body sheet was sandwiched with a release film and pressed under the conditions of a pressure of 0.5 MPa, a temperature of 87° C., and a time of 3 minutes to produce a thermally conductive sheet sample.

[0162] Table 1 shows the evaluation results of the thermally conductive sheet samples. The release film on one side of the sample was peeled off and the one side was placed on a SUS plate inclined at 45°. As a result, the sample moved, and it was confirmed that one side had no stickiness. In addition, the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°. As a result, the sample moved, and it was confirmed that the other side had no stickiness either.

[0163] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 0.8 mm.

[0164] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.35°C·cm 2 / W.

[0165] [Comparative Example 2]

[0166] In a two-component addition reaction type liquid silicone, 42% by volume of alumina particles with an average particle size of 5μm coupled with a silane coupling agent and 23% by volume of pitch-based carbon fibers with an average fiber length of 150μm as a fibrous thermal conductive filler are mixed to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a silicone resin with an organopolysiloxane as the main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 20.3vol%:14.7vol%. The obtained silicone composition is extruded in a hollow quadrangular prism-shaped mold (50mm×50mm) with a peeling film attached along the inner wall, and after being formed into a 50mm square silicone molded body, it is heated in an oven at 100°C for 6 hours to prepare a silicone cured product (thermally conductive molded body). After the silicone cured product is taken out from the hollow quadrangular prism-shaped mold, the peeling film is peeled off and cut with a slicer to a thickness of 0.3mm. The cut molded product sheet was sandwiched between release films and pressed under conditions of a pressure of 0.5 MPa, a temperature of 87° C., and a time of 3 minutes to produce a thermally conductive sheet sample.

[0167] Table 1 shows the evaluation results of the thermally conductive sheet samples. When the release film on one side of the sample was peeled off and one side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that one side had stickiness. In addition, when the release film on the other side of the sample was peeled off and the other side was placed on a SUS plate inclined at 45°, the sample did not move, thereby confirming that the other side also had stickiness.

[0168] The sample shape is processed into a thickness of 0.3mm. Thermally conductive sheet The metal clamp is adjusted to apply 4.0kgf / cm 2 After standing at 80°C for 72 hours, The distance (protrusion amount) of the thermally conductive sheet protruding from the metal is a maximum of 1.6 mm.

[0169] For the sample, a 1.5 kgf / cm 2 The thermal impedance was measured with a load of 0.26°C·cm 2 / W.

[0170] [Table 1]

[0171]

[0172] As shown in Table 1, by peeling off the release film on one side of the sheet after pressing and leaving it to stand, non-adhesiveness can be imparted to one side of the sheet.

Claims

1. A method for producing a thermally conductive sheet, wherein one side of the sheet body is non-adhesive and the other side is adhesive, comprising the following steps: A step of forming a thermally conductive molded body by molding a thermally conductive resin composition containing a thermally conductive filler in a binder resin into a predetermined shape and curing the composition; The step of cutting the thermally conductive molded body into sheets to form a molded body sheet; A step of attaching release films to both sides of the molded sheet and pressing the molded sheet so that both sides of the molded sheet are covered with uncured components of the adhesive resin that have seeped out from the sheet body of the molded sheet, thereby imparting adhesiveness to both sides of the molded sheet; a step of peeling the release film from one side of the molded body sheet, removing uncured components of the binder resin from the one side, and imparting non-adhesiveness to the one side of the molded body sheet; and A step of attaching a new release film to the side from which the uncured component of the binder resin has been removed.

2. The method for producing a thermally conductive sheet according to claim 1, wherein after the release film is peeled off from the one side of the molded sheet, the molded sheet is left to stand for a predetermined time under an atmospheric pressure atmosphere to remove uncured components of the binder resin from the one side of the molded sheet.

3. The method for producing a thermally conductive sheet according to claim 1, wherein after the release film is peeled off from the one side of the molded sheet, the molded sheet is allowed to stand in a heat-dried or reduced-pressure atmosphere to remove uncured components of the binder resin from the one side of the molded sheet. 4 . The method for producing a thermally conductive sheet according to claim 1 , wherein the peeling strength of the release film attached to the one surface is higher than the peeling strength of the release film attached to the other surface. 5 . The method for producing a thermally conductive sheet according to claim 1 , wherein the binder resin is a liquid silicone component, and the thermally conductive filler is carbon fiber. 6 . The method for producing a thermally conductive sheet according to claim 5 , wherein the liquid silicone component comprises a silicone liquid A component as a main agent and a silicone liquid B component containing a curing agent, and the amount of the silicone liquid A component contained is greater than that of the silicone liquid B component. 7 . The method for producing a thermally conductive sheet according to claim 1 , wherein the molded sheet has a thickness of 0.2 mm to 0.5 mm.

8. The method for producing a thermally conductive sheet according to any one of claims 1 to 3, wherein the circular thermally conductive sheet having a diameter of 19 mm and a thickness of 0.3 mm is sandwiched between a cylindrical metal having a diameter of 20 mm and a height of 12 mm, and the thermally conductive sheet is adjusted so as to be subjected to a pressure of 4.0 kgf / cm 2 After the load was applied, the columnar metal was left to stand at 80° C. for 72 hours, and the distance by which the thermally conductive sheet protruded from one end surface of the columnar metal was less than 1.3 mm.

Citation Information

Patent Citations

  • Ultrasonic probe

    JP1982052299A

  • Detecting method for breaking of flexible film of product

    JP1982066335A

  • Adhesive heat-conductive sheet

    JP2010093077A

  • Resin sheet and production method of the same, resin sheet cured product, and heat radiation component

    JP2014009343A

  • Heat conduction sheet and manufacturing method of the same

    JP2014216399A